Metode Penugasan Disertai Umpan Balik Terhadap Hasil Belajar Matematika Siswa dalam Menyelesaikan Soal Operasi Bilangan Bulat - Azis Azis; Maya Nurlita (Jurnal Akademik Pendidikan Matematika, 2021)
The purpose of this study was to determine the difference in the average learning outcomes of students who were taught the assignment method with feedback and those taught the assignment method without feedback in solving integer operations for class VII students of SMP Negeri 7 Baubau. This research is a quasi-experimental research (quasy experimental) with a quantitative approach. The population used in this study were all Grade VII students of SMP Negeri 7 Baubau who were spread in 3 parallel classes with a total of 93 people. To determine which class is the experimental class and the control class, the three classes are drawn by lot. Selected as the experimental class is class VII B and class VII A as control class. This research was conducted in the odd semester of the 2019/2020 school year. The instrument in this study was a test of mathematics learning outcomes. Data were analyzed by prerequisite test which consisted of normality test and data homogeneity test. The results showed that there was a difference in the average learning outcomes of students who were taught the assignment method with feedback and those taught the assignment method without feedback in solving integer operations for class VII students of SMP Negeri 7 Baubau. This is indicated by the value of t_count = 4.310 and the value of sig. (2-tailed) 0.000 < 0.05, meaning that H0 is rejected.